SEBUAH PEMBELAJARAN UNTUK PEMILU YANG AKAN DATANG - Nurida Maulidia Rahma (Jurnal Penelitian Politik, 2022)
The general election is a means for the nation and state to carry out democracy (Effendi, 2017). However, with the condition of freedom of democracy that tends to be wildly out of control, the implementation of elections is quite worrying. Therefore, it is necessary to monitor and evaluate the election to improve the electoral system. Through his book, Muhammad Nizar Kherid has evaluated the electoral system in Indonesia from 1955 to 2019. This book use the theory of legal pluralism to evaluate the electoral system in Indonesia since this theory is considered an effective theory in evaluating the electoral system. The results of the analysis show that the most ideal electoral system in Indonesia between 1955-2019 is the 1955 election system.